A transient model for temperature prediction in a salt-gradient solar pond and the ground beneath it. (1st August 2017) - Amigo, José; Meza, Francisco; Suárez, Francisco
Abstract: Salt-gradient solar ponds are cost-effective long-term solar collectors that can store low-grade heat and deliver it continuously. For design and operation purposes, it is important to develop computational tools that can represent energy fluxes at the interface between the bottom of the pond and the ground beneath it. In this study, a robust one-dimensional transient model is developed to represent the thermal evolution of a salt-gradient solar pond and the ground that surrounds it. The model was evaluated under different contrasting scenarios: buried or unburied ponds, artificially or naturally heated ponds and for deep or shallow groundwater tables. Experimental data from an indoor laboratory-scale solar pond were used for the development, calibration and validation of the model. A good agreement between experimental and modeled results was observed, with a root mean square error (RMSE) of 1.21 °C and 1.54 °C for the upper and lower convective zones respectively, during a 28-days validation period. Further, the model was validated using experimental data from three outdoor salt-gradient solar ponds obtaining RMSEs that ranged between 1.5 and 6.5 °C. Results show that dividing the ground into multiple layers contributes to the robustness of the model, as it allows the representation of the ground heat storage. Highlights: A one-dimensional transient model is developed. Representation of the thermal dynamics in a solar pond and the ground beneath it. Calibration and validation of the model with an experimental setup. Validation of the model with three literature solar pond measurements. Ground heat storage can be represented with the model.